Students’ Perception of Automated Written Corrective Feedback Provided by Grammarly in Enhancing Writing Skills - Aruna, Hanif Muti; Sarosa, Teguh (ELE Reviews: English Language Education Reviews, 2025)
Feedback on students’ writing is important to improve the students’ writing quality. However, due to the limited time for interaction with the lecturer during writing lessons, the lecturer may struggle to provide comprehensive feedback to students regarding their errors. One solution is to use Grammarly as an automated tool for written corrective feedback. This research aims to investigate students’ perceptions of automated written corrective feedback provided by Grammarly in English as a Foreign Language (EFL) writing classes and to examine students’ responses to Grammarly feedback when they receive it. This research was qualitative. The research participants were three EFL undergraduate students who had joined an Academic Writing class at one of the universities in Surakarta. This research employed the narrative inquiry method, gathering data through a narrative frame, semi-structured interviews, and document analysis. This research used purposive sampling for the research participants and interactive model analysis to analyze the data. The findings reveal that students generally find Grammarly a valuable and accessible tool that enhances their writing by providing immediate corrections for grammatical errors. However, there are mixed feelings about the appropriateness of some feedback, and students often feel the need to double-check Grammarly’s suggestions. The students also perceive that Grammarly does not always give appropriate feedback and that Grammarly has some features that require a subscription to Grammarly Premium. Moreover, the students’ responses are by accepting the feedback from Grammarly and paying attention to the explanation of the feedback. Its effectiveness relies on students critically proofreading their suggestions to ensure they are correct. This research can benefit students who learn English as a foreign language and as a second language in writing classes. The implications suggest that integrating automated written corrective feedback, such as Grammarly, can address time constraints in learning activities while enhancing self-learning, writing skills, and engagement.